Can APC mutation analysis contribute to therapeutic decisions in familial adenomatous polyposis? Experience from 680 FAP families. Issue 4 (1st April 2001) - Friedl, W; Caspari, R; Sengteller, M; Uhlhaas, S; Lamberti, C; Jungck, M; Kadmon, M; Wolf, M; Fahnenstich, J; Gebert, J; Möslein, G; Mangold, E; et al.
Abstract : BACKGROUND AND AIMS: In familial adenomatous polyposis (FAP), correlations between site of mutation in the adenomatous polyposis coli ( APC ) gene and severity of colonic polyposis or extracolonic manifestations are well known. While mutation analysis is important for predictive diagnosis in persons at risk, its relevance for clinical management of individual patients is open to question. METHODS: We examined 680 unrelated FAP families for germline mutations in the APC gene. Clinical information was obtained from 1256 patients. RESULTS: APC mutations were detected in 48% (327/680) of families. Age at diagnosis of FAP based on bowel symptoms and age at diagnosis of colorectal cancer in untreated patients were used as indicators of the severity of the natural course of the disease. A germline mutation was detected in 230 of 404 patients who were diagnosed after onset of bowel symptoms (rectal bleeding, abdominal pain, diarrhoea). When these patients were grouped according to the different sites of mutations, mean values for age at onset of disease differed significantly: patients carrying APC mutations at codon 1309 showed a disease onset 10 years earlier (mean age 20 years) compared with patients with mutations between codons 168 and 1580 (except codon 1309) (mean age 30 years), whereas patients with mutations at the 5′ end of codon 168 or the 3′ end of codon 1580 were diagnosed at a mean age of 52 years. Within each group of patients however large phenotypic variation was observed, even among patients with identical germline mutations. A higher incidence of desmoids was found in patients with mutations between codons 1445 and 1580 compared with mutations at other sites, while no correlation between site of mutation and presence of duodenal adenomas was observed. CONCLUSIONS: As age at manifestation and course of the disease may be rather variable, even in carriers of identical germline mutations, therapeutic decisions should be based on colonoscopic findings in individual patients rather than on the site of mutation. However, in patients with mutations within codons 1445–1580, it may be advisable to postpone elective colectomy because desmoids may arise through surgical intervention.